MHD and Radiation Effects on Natural Convection Flow in a Porous Medium past an Infinite Inclined Plate with Ramped Wall Temperature: An Exact Analysis - Zulkhibri, Ismail; Hussanan, Abid; Khan, Ilyas; Sharidan, Shafie (CESER Publications, 2013)
The unsteady magnetohydrodynamic (MHD) free convection flows in a porous medium past an infinite inclined plate with ramped wall temperature are considered. Exact solutions using the Laplace transform technique are obtained for the velocity and temperature fields. Expressions for nondimensional skin-friction and Nusselt number has been formulated. The influence of various embedded flow parameters such as Prandtl number, inclination angle, magnetic field parameter, Grashof number, radiation parameter and time on velocity and temperature have been analyzed through graphs and discussed.